Menjaga Kebersihan Lingkungan Dengan Melakukan Pengelolaan Sampah di SDK Lamablawa, Desa Lamablawa, Kecamatan Witihama Kabupaten Flores Timur - Gregoriana Maria Da Silva Hale; Kristianus Hale Molan; Frans Nyong (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Maintaining the school environment is the responsibility of each individual to keep the environment clean and comfortable by doing waste management properly. Waste management is the activity of sorting waste according to its type, namely organic waste and non-organic waste. However, there are still many people who do not understand the importance of protecting the school environment by littering. Therefore, in this community service program, waste cleaning activities will be carried out in the SDK Lamablawa environment. The purpose of this activity is to increase the awareness and role of SDK Lamablawa students and teachers in maintaining cleanliness in the school environment. The implementation methods are observation, socialization, installation of daily picket rosters and cleanliness posters, and trash bins, as well as the action of cleaning the school environment with the students and students of SDK Lamablawa and the teachers of SDK Lamablawa who are very enthusiastic. with this activity can help them overcome the problem of waste in the SDK Lamablawa environment.